Driving distraction at night: The impact of cell phone use on driving behaviors among young drivers. (November 2022) - Yan, Yingying; Zhong, Shiquan; Tian, Junfang; Song, Liang
Highlights: The interaction effect between time of day and distractions on driving was verified. Distracted drivers had greater SDLP at night than during daytime on some roads. The speed under the phone distractions was higher at night on small-radius curves. In daytime, SDLP during talking was less than under no distraction in some scenarios. Novice drivers had higher driving speed than experienced drivers under talking. Abstract: Currently, young drivers are more likely than other drivers to use cell phones while driving at night, which has become a major cause of road crashes. However, limited attention has been given to distracted nighttime driving. Therefore, the aim of this study was to explore the interaction effect of cell phone use and time of day (daytime and nighttime) on young drivers' car-following performance. Forty-three young drivers engaged in a driving simulator experiment with a within-subject design that included three distractions (no distraction, talking and texting on a cell phone) and two times of day. This paper applied non-parametric tests to analyze the data and obtained the following results: (1) the standard deviation of lane position (SDLP) did not significantly differ at either time of day under no distraction, but it was significantly higher at night on straight roads and large-radius curves after introducing distractions. In addition, participants drove faster and gave less headway on small-radius curves under both distractions at night; (2) texting significantly increased the SDLP, while there was less lateral variation during the talking tasks than under no distraction on simple road sections; and (3) compared with the experienced drivers, the novice drivers drove faster during the talking tasks on small-radius curves, but there was no significant difference between groups during the texting tasks. These findings provide both theoretical and practical implications for related policy makers to enhance traffic safety.